The reform of legal capacity: Some theoretical notes on its justification - Smith, Pamela (2020)
The last Peruvian reform on legal capacity, established in the Peruvian Civil Code, opened the way to the recognition of this right under equal conditions for the group of people with disabilities. This formal recognition has a particular impact on those persons with intellectual and psychosocial disabilities who had historically been considered as objects and not as subjects of this right. This normative modification generates a profound change in the theoretical-political concepts regarding legal capacity that must be addressed by civil dogmatic and the disciplines compromised. We consider it of transcendental importance to carefully observe the theoretical change behind the reform, in order to facilitate the understanding of its real magnitude and to recognize the turning points in our legal theory. Moreover, because we are in the process of implementing this new legislation. If such special care is not taken, there is a risk that this change will generate in our legal reality a non-coherent and non-uniform effect in which it will not be possible to concretely achieve the new recognitions and freedoms.